Production and Characterization of Cellulase enzymes of Xanthomonas campestris pv. sesami - Gubara1, Weam; Abdel-Rahim1, Awad (Gezira Journal of Engineering and Applied Sciences; مجلد 13 عدد 2 (2018), 2019)
The bacterium Xanthomonas campestris pv. sesami , is the causal organism of the leaf spot disease (Marad eldum) in sesame plants. Enzymes are protein molecules that catalyze chemical reaction.  Cellulase enzymes which were reported to be produced by many plant pathogenic bacteria, were found to play an important role in pathogenesis. The present study was aimed to investigate the capacity of the bacterium X. campestris pv. sesami , to produce the two cellulase enzymes. (Carboxymethylcellulase, C x , and Cellobiase). A salt medium supplemented with different cellulose, materials was tested for the production of the enzymes, using viscosity reducing and reducing  group methods. The produced enzymes were characterized using different selective tests. The results showed that no cellobiase was produced in any of the substrates and only the (C x ) was produced by the bacterium. Carboxymethyl- cellulose was found as the best substrate giving 49.0 enzyme units (mg/ ml glucose). When the incubation time was tested, the enzyme activity was found maximum at the 7 th and 8 th days, giving 9.3 and 9.6 viscosity units respectively. The pH optimum of the enzyme activity was found  at pH 6.0 which gave 18.0 viscosity units compared to only 5.1 at pH 4.0 and 2.8 at pH 10.0. The results also showed that the optimum degree of temperature for the enzyme activity was at 40.0 0 C.  Different metallic ions were tested for their effects on the enzyme activity, Ca ++ , K ++ and Mn ++ were found effective giving enzyme activities of 104.5, 99.5 and 92.2 enzyme unit( mg/ml glucouse), respectively. The C x enzyme was reported to play an important role in the bacterial leaf spot diseases of plants. The tested bacterium should be investigated for the production of the pectic and hemicellulase enzymes which were also found to have a role in the pathogenesis process.